The Predictive Ability of Child Characteristics and Parenting Factors on Four Developmental Domains in Toddlers - Melly Latifah; Dwi Hastuti; Neti Hernawati; Reisi Nurdiani; Raihan ‘Ainun Hasanah (Fakultas Ilmu Keperawatan Universitas Indonesia, 2026)
Stunting is a chronic condition that has a significant impact on child development. This phenomenon is primarily caused by prolonged nutritional deficiency, especially during the first 1,000 days of life. In addition, as family factors also play a crucial role in children’s development, this study aims to analyze the influence of child and family characteristics, mother–child attachment, parenting practices, and the nutritional status of children (stunted/non-stunted) on children’s gross motor, fine motor, language, and personal–social skills. This study used a quantitative design with an explanatory approach involving 202 mother–child pairs with children aged 12–36 months. The findings show that healthcare practices (p = 0.016) and male gender (p = 0.050) significantly affected gross motor development (AR² = 0.068), while toddler age (p < 0.001), stunting status (p < 0.001), and healthcare practices (p = 0.042) affected fine motor development (AR² = 0.213). Healthcare practices (p = 0.021) significantly affected language development (AR² = 0.038), while toddler age (p < 0.001), mother–child attachment (p = 0.025), and healthcare practices (p = 0.010) significantly affected personal–social development (AR² = 0.138). Thus, addressing stunting requires cooperation from various stakeholders—including the government, healthcare professionals, the community, and parents—to focus on child- and family-centered approaches.